Battery Pack Sizing Based on Experimental Characterization and Simulation Validation - Aline Raquel Lily Drivet-Gonzalez; Riccardo Cespi; Juan C. Tudon-Martinez; Jorge De-J. Lozoya-Santos (IEEE Access, 2024)
Electrification of internal-combustion-engine vehicles represents a common requirement for urban areas interested in reducing the quantity of air pollution and toxic gas emissions. Along with the transition of private solutions toward individual mobility with electric cars, vehicle electrification for community mobility reaches a high additional value of the atmospheric decarbonization global objective. To this aim, this paper presents both experimental and simulation approaches, for vehicle electrification of student mobility at Tecnológico de Monterrey, where dedicated transportation operates several times a day. The driving cycle and the road slope are determined by making use of GPS based mobile apps first. Then, the daily energy consumption is calculated, and the battery sizing is defined by comparing several electric cells. The safer battery is chosen, and the internal resistance and open-circuit voltage are then characterized with experimental tests.The paper presents a methodology for accurately assessing the energy demands of electric buses. These findings provide insights for battery pack design and selection based on driving cycles and energy requirements, which may be used to accelerate the electrification of bus routes or scale it to large bus fleets. Finally, a co-simulation with Matlab/Simulink and CarSim shows the behavior of the electric powertrain highlighting the quality and performances of the obtained results.